2019
DOI: 10.1016/s2095-3119(18)62062-3
|View full text |Cite
|
Sign up to set email alerts
|

Supplemental blue and red light promote lycopene synthesis in tomato fruits

Abstract: Lycopene, one of the strongest natural antioxidants known and the main carotene in ripe tomato, is very important for human health. Light is well known to be one of the most important environmental stimuli influencing lycopene biosynthesis; specifically, red light induces higher lycopene content in tomato. However, whether blue light promotes lycopene synthesis remains elusive and exactly how light stimulation promotes lycopene synthesis remains unclear. We applied supplemental blue and red lighting on tomato … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

6
49
0
1

Year Published

2019
2019
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 62 publications
(56 citation statements)
references
References 34 publications
(43 reference statements)
6
49
0
1
Order By: Relevance
“…In this study, the effect of blue-light irradiation on lycopene concentration in fruit was measured during cultivation. Although the effects of blue-light irradiation on lycopene concentration have been investigated in previous reports [ 46 , 47 ], their experimental conditions were different from this study. The effects of supplemental blue light over a long period after flowering in a greenhouse [ 46 ] and blue-light irradiation after harvest [ 47 ] have been investigated in previous reports.…”
Section: Discussionmentioning
confidence: 83%
“…In this study, the effect of blue-light irradiation on lycopene concentration in fruit was measured during cultivation. Although the effects of blue-light irradiation on lycopene concentration have been investigated in previous reports [ 46 , 47 ], their experimental conditions were different from this study. The effects of supplemental blue light over a long period after flowering in a greenhouse [ 46 ] and blue-light irradiation after harvest [ 47 ] have been investigated in previous reports.…”
Section: Discussionmentioning
confidence: 83%
“…Alba et al (2000) reported that red light promotes and far-red light reduces lycopene biosynthesis and that this effect is mediated by photochromes. Xie et al (2019) have analyzed tomatoes exposed to blue and red LEDs on a gene expression level using qRT-PCR. They found out that blue and red light increased the lycopene concentration in tomatoes by inducing light receptors that modulate phytochrome-interacting factors and ELONGATED HYPOCOTYL 5 activations to mediate phytoene synthase 1 (PSY).…”
Section: Effects On Carotenoids Of Tomatoesmentioning
confidence: 99%
“…Additional far-red light in combination with red LEDs and HPS appears to increase total fruit number. It has also been shown that the exposure to supplementary red and blue LED lighting increases the lycopene and ß-carotene content (Xie et al, 2019;Ngcobo et al, 2020).…”
Section: Introductionmentioning
confidence: 99%
“…However, tomato fruit is also important in the human diet because it can provide vitamins and a wide range of bioactive molecules [2], such as vitamins C and E, flavonoids, and phenols [3]. Lycopene is one of the strongest natural antioxidants known and is the main carotene in ripe tomatoes [4], and together with β-carotene, it is effective in eliminating peroxyl radicals [5]. These compounds seem to play a…”
Section: Introductionmentioning
confidence: 99%